2001
DOI: 10.1016/s0022-2860(00)00787-0
|View full text |Cite
|
Sign up to set email alerts
|

Transient absorption spectra of triplet states and charge carriers of conjugated polymers

Abstract: The use of pulse radiolysis to study transient species in conjugated polymers in solutions is discussed, with particular reference to poly(2-methoxy-5-(2 0 -ethylhexoxy)-p-phenylenevinylene) (MEH-PPV). The excited triplet state is speci®cally generated by energy transfer on radiolysis of benzene solutions in the presence of suitable sensitisers, and its spectrum is reported. The presence of vibronic structure suggests a localised triplet state. By varying the energy of the sensitiser, it is possible to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 47 publications
(55 reference statements)
3
16
0
Order By: Relevance
“…The triplet-triplet absorption of Ph-LPPP shows an indefinite vibronic structure, which is probably indicated for the coupling of the C-C stretch modes [16] of the conjugated backbone. The PIA of Ph-LPPP is very similar to what have been reported for other conjugated polymers [17,18] at low temperatures using the same technique. Triplet state has more localized character due to restrictions of transition from singlet to triplet state due to spin conservation [19,20].…”
Section: Resultssupporting
confidence: 85%
“…The triplet-triplet absorption of Ph-LPPP shows an indefinite vibronic structure, which is probably indicated for the coupling of the C-C stretch modes [16] of the conjugated backbone. The PIA of Ph-LPPP is very similar to what have been reported for other conjugated polymers [17,18] at low temperatures using the same technique. Triplet state has more localized character due to restrictions of transition from singlet to triplet state due to spin conservation [19,20].…”
Section: Resultssupporting
confidence: 85%
“…We have previously reported spectra and energies of the triplet states of these polymers generated in this way [26,27,31,41]. The technique has also been used to study some p-phenylenevinylene oligomers [51] and broken conjugation polymers [52].…”
Section: Pulse Radiolysis/energy Transfermentioning
confidence: 99%
“…Knowledge of the formation and decay pathways of these triplets is therefore important for a full understanding of the electroluminescence behaviour of conjugated organic polymers. We report results of polymer triplet state dynamics in dilute solution, under conditions where they can be considered to be isolated chains [31], i.e., where there are no interchain interactions, and where the time between collisions of two polymer molecules is longer than the lifetimes of the excited states being studied. Preparation of triplet states by both photoexcitation and energy transfer will be considered.…”
Section: Introductionmentioning
confidence: 99%
“…18 It has also been demonstrated, however, that such optical studies may be complicated by the fact that different types of excitons and charges may have very similar spectral signatures. [18][19][20][21][22] THz time-domain spectroscopy ͑THz-TDS͒ therefore ideally complements optical studies, as it allows one to directly probe both exciton and free charge species simultaneously: it is sensitive to the real and imaginary components of frequency-dependent ͑0.2-1.5 THz͒ photoconductivity and, as such, can monitor free and bound charges on a subpicosecond timescale. Our initial THz-TDS studies 5 of semiconducting polymers have indicated that excitons are the primary photoexcitation product, while only a small number of free charges are formed on ultrafast times, most likely from dissociation of "hot" excitons.…”
Section: Introductionmentioning
confidence: 99%